Solid electrolyte membranes based on polybenzimidazole containing graphitic carbon nitride moiety (PBICN) for high-temperature fuel cell applications. (19th November 2021) - Kim, Eun-Ki; Cho, Kyunghwa; Lee, Hyungseok; Chung, In; Lee, Jong-Chan
Abstract: Polybenzimidazole containing graphitic carbon nitride moiety (PBICN) is prepared by in situ polymerization of 3, 3′-diaminobenzidine (DAB), isophthalic acid (IPA), and graphitic carbon nitride (g-CN) for the application in high-temperature fuel cell membrane. Since g-CN has a nanosheet structure and lots of amine end groups, it can be involved in the polymerization process producing PBI-grafted g-CN. The PBICN membrane shows much improved thermal property, oxidative stability, mechanical strength, and proton conductivity compared to pristine PBI membrane and the PBI composite membrane prepared simply by mixing PBI and g-CN. In addition, it is confirmed that the PBI-grafted g-CN structure formed during the in situ polymerization can contribute to the increase of the dimensional stability for the PBICN membrane. Especially, PBICN membrane prepared by the in situ polymerization using g-CN exhibits much improved fuel cell performance. For example, the power density value of the membrane electrode assembly (MEA) fabricated using PBICN membrane prepared using 0.5 wt% of g-CN is 400 mW cm −2, which is much larger than those of MEA fabricated using PBI membrane (241 mW cm −2 ) and the PBI composite membrane containing 0.5 wt% of g-CN (326 mW cm −2 ) membrane during the fuel cell performance test performed at 160 °C without humidification. Graphical abstract: Image 1 Highlights: Synthesis of polybenzimidazole containing graphitic carbon nitride moiety (PBICN). Formation of PBI-grafted g-CN structure by in situ polymerization method. Systematic studies of the filler effects on the performance of PBI electrolyte membrane. Improved physicochemical properties of PBICN membrane. Outstanding cell performance of MEA prepared with PBICN membrane.